Adaptive potential of the hulled oats gene pool according to 1000-grain weight - M. V. Tulyakova; G. A. Batalova; S. V. Permyakova (Зерновое хозяйство России)
There have been presented the study results of 11 collection hulled oats samples in comparison with the standard variety ‘Krechet’ conducted at the Falenskaya selection station of the FARC the North-East (the Kirov region) in 2018–2020. The purpose of the current study was to identify sources stable on the trait ‘1000-grain weight’ for the breeding of hulled oats by estimating the adaptability parameters. The soil of the experimental plot was sod-podzolic, medium loamy, the meteorological conditions were contrasting in temperature and precipitation. In the favorable year of 2019, the 1000-grain weight was the highest (34.6–45.9 g), the index of environmental conditions was positive (Ij = 1.6). In the unfavorable year of 2020, the 1000-grain weight was 31.3–41.8 g and the index of environmental conditions was negative (Ij = -1.5). There have been identified the adaptable sources (IEP = 1.08–1.00) ‘15330 KSI 590/05’ (Russia), ‘15388 Saltaret’ (Moldova), ‘15423 Prelekst’, ‘15426 Werva’ (Germany); the stable sources according to the relative stability of the trait (St2 = 0.99–0.91) ‘15280 55 h 2106’, ‘15331 CSI 2167/03’ (Russia), ‘15297 Geszti’ (Hungary), ‘15388 Saltaret’ (Moldova), ‘15428 Bohum’ (Poland), ‘15420 Leniak’ (Germany); the sources with a high level of intensity (I = 24.5 and 19.30%) – ‘15329 CSI 639/05’, ‘15330 CSI 590/05’ and homeostaticity (Hom = 25.28–11.96) ‘15280 55 h 2106’ (Russia), ‘15297 Geszti’ (Hungary), ‘15388 Saltaret’ (Moldova); the sources responsive to favorable growing conditions (Kp = 1.11–1.28) ‘15329 KSI 639/05’, ‘15330 KSI 590/05’, ‘15331 KSI 2167/03’ (Russia), ‘15414 Enostar’ (Germany); the most adaptive sources in terms of the sum of ranks ‘15330 CSI 590/05’ and ‘15329 CSI 639/05’ (Russia), ‘15388 Saltaret’ (Moldova), ‘15426 Werva, ‘15414 Enostar’ (Germany). There have been identified significant direct correlations between indicators of stability and homeostaticity (r = 0.96), intensity and coefficient of responsiveness (r = 0.73).